Noninvasive device readouts validated by immunohistochemical analysis enable objective quantitative assessment of acute wound healing in human skin. Issue 6 (4th November 2015) - Ud‐Din, Sara; Greaves, Nicholas S.; Sebastian, Anil; Baguneid, Mohamed; Bayat, Ardeshir
ABSTRACT: Objective evaluation of cutaneous wounds through use of noninvasive devices has important implications for diagnosis, monitoring treatment efficacy, progression and may lead to development of improved theranostic treatment strategies. However, there is a lack of validation in the use of certain devices in wound repair, where objective measurements taken by noninvasive devices have been corroborated by immunohistochemical analysis. Thus, data from three acute wound‐healing studies in healthy volunteers using three noninvasive objective devices were further evaluated by immunohistochemistry. One hundred ten participants had 5‐mm diameter skin biopsies to their arms. Spectrophotometric intracutaneous analysis (SIAscopy), full‐field laser perfusion imaging, and three‐dimensional imaging provided quantitative measurements of melanin, hemoglobin, collagen, blood flow, and wound size; all of which were validated by immunohistochemistry. Full‐field laser perfusion imaging showed blood flow increased to D7 and decreased by 40% to D14. SIAscopy showed that hemoglobin increased to D7 and reduced to D14. CD31 analysis corroborated this by showing a 76% increase in blood vessel density to D7 and a reduction by 14% to D14. Three‐dimensional imaging showed that wound surface area reduced by 50% from day 7 to day 14. Alpha‐smooth muscle Actin (Alpha‐SMA) staining supported these trends by showing increased levels by 72% from D0 to D14 (corresponding to wound contraction). Collagen, measured by SIAscopy, decreased to D7 and increased to D14, which was validated by collagen III analysis. Additionally, collagen I increased by 14% from D0 to D14. SIAscopy measurements for melanin showed an increase at D7 and a slight reduction to D14, while melanogenesis increased by 46.7% from D0 to D14. These findings show the utility of noninvasive objective devices in the quantitative evaluation of wound‐healing parameters in human skin as corroborated by immunohistochemistry. This may contribute to the development of prognostic parameters for assessment of response to wound therapy.